2021
DOI: 10.34067/kid.0006102020
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in Spent Dialysate from Chronic Peritoneal Dialysis Patients with COVID-19

Abstract: Background To date it is unclear whether SARS-CoV-2 is present in spent dialysate from peritoneal dialysis (PD) patients with COVID-19. Our aim was to assess the presence or absence of SARS-CoV-2 in spent dialysate from chronic PD patients with confirmed diagnosis of COVID-19. Methods Spent PD dialysate samples from COVID-19 positive PD patients were collected between March and August 2020. The multiplexed real-time reverse transcriptase-polymerase chain reaction assay contained primer/probe sets specific to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Lastly, since spring 2020, clinic staff are actively involved in quality improvement and clinical research projects related to COVID-19. 3,4 We believe that these factors in aggregate contributed to the high vaccination acceptance rate observed by us.…”
mentioning
confidence: 80%
“…Lastly, since spring 2020, clinic staff are actively involved in quality improvement and clinical research projects related to COVID-19. 3,4 We believe that these factors in aggregate contributed to the high vaccination acceptance rate observed by us.…”
mentioning
confidence: 80%
“…Later analysis in a separate study demonstrated negative qRT‐PCR results for the SARS‐CoV‐2 RNA‐dependent RNA polymerase (RdRp) and Envelope (E) genes in a total of 11 PD effluent samplings across three patients with mild to moderate COVID [78]. Since August 2020, a handful of studies across the world supported these findings by similarly reporting an absence of detectable SARS‐CoV‐2 RNA in spent PD effluent [20, 84–87]. Perhaps most convincingly, SARS‐CoV‐2 RNA was undetectable in qRT‐PCR analysis of spent PD dialysate samples from 10 patients with severe COVID‐19 pneumonia; this same paper also reported an absence of infective virions, cytopathic effects in culture, and plaque formation in PD effluent [88].…”
Section: Sars‐cov‐2 In Peritoneal Dialysis Effluentmentioning
confidence: 99%
“…As reported previously, all PD dialysate samples in Group 3 and Group 4 were tested negative for SARS-CoV-2 viral RNA. 6,7 We had no access to serum SARS-CoV-2 antibody levels in any patient.…”
mentioning
confidence: 99%